Early childhood education: key competences in teacher education - Lino, Dalila (2022)
Teacher education is a complex field and requires high levels of specialization in diverse fields of knowledge. The formal preparation of early childhood teachers involve education in general aspects of teacher education, but requires a focus on specific components for a teaching that has its own specificity. Work with young children entail high levels of commitment, knowledge, skills and attitudes that should be developed in pre-service teacher education. The literature in early childhood teacher education highlights a number of key components including: general educational, professional foundations, formal knowledge and practice, and curriculum development. This paper aims to analyze the key components of early childhood teacher education programs and discuss their role on the preparation of competent and efficient teachers for a demanding 21st century society.